(untitled) (Docentes 2.0 Journal, 2026)
Chilean early childhood education has more than 160 years of development and institutionalization. Currently, this educational level faces new pedagogical and social challenges derived from increasing migratory flows. The objective of this essay was to propose a Social Justice Matrix for migrant children in early childhood education, with indicators related to rights and diversity management. This essay follows a qualitative and interpretive approach, with a narrative design and a thematic focus. It presents a brief historical overview of the legal, educational, and migration frameworks that guarantee migrant children’s right to education. The proposed Social Justice Matrix operationalizes Axel Honneth’s concept of recognition across the three spheres formulated by the author: family, State, and society. Each sphere is broken down into indicators based on national pedagogical standards, with the purpose of assessing and monitoring processes related to social justice recognition within the pedagogical practices developed by educational communities in early childhood education institutions. This Matrix offers an interpretive reading of regulatory frameworks and helps reframe educational practices to advance toward equitable learning environments that are sensitive to diversity and protective of early childhood rights. Finally, the essay presents its conclusions, theoretical implications, limitations, and future lines of research.